The new ICD-11 diagnosis of personality disorder in forensic psychiatry - Jantzi, Camille; Moulin, Valerie (Frontiers in Psychiatry, 2025)
This paper examines the implications of the transition from ICD-10 to ICD-11 for the diagnosis of personality disorders in forensic psychiatric evaluations. The ICD-11 introduces a dimensional approach, replacing the previous categorical system with a focus on severity and maladaptive personality traits. This shift addresses longstanding criticisms of the ICD-10, such as underdiagnosis, diagnostic instability, and lack of scientific validity. The new model classifies personality disorders by severity (mild, moderate, severe) and five trait domains, enhancing clinical nuance but also introducing challenges in continuity and communication. While the ICD-11 aims to improve diagnostic accuracy and treatment planning, concerns remain regarding overdiagnosis, increased stigma-especially among adolescents and the adequacy of trait coverage. The absence of validated diagnostic tools and clear severity thresholds further complicates forensic application. Preliminary studies suggest a dramatic increase in diagnosed cases under ICD-11, raising questions about the risk of pathologizing normative behavior and the potential for excessive intervention. The paper highlights the need for further research and careful implementation to balance improved recognition of personality pathology with the avoidance of unintended negative consequences in forensic practice.